Botanical expedition in mountains of Caucasus in 2013 - Firsov, Gennady A. (Conservation Science, 2017)
Summary [editor’s note] The botanical expedition has an important role in documenting unknown flora and its natural history. Such expedition has been instrumental to ascertain what conservation actions the region need of. Gennady A. Firsov writes a short note providing a fascinating account of a botanical expedition in the Caucasus Mountains. His vivid account of geography, climate and flora provide a resemblance between floral diversity with that of physical geography and climate. The six member expedition team visited the highest peak of Caucasus, the Bermamyt plateau, Teberda and Tuman- Lykyel Lake. Teberda, in particular, is a unique floral sanctuary where three seasons can be witnessed at the same time: warm summer down the valley, early spring in alpine meadow and winter further up with snowy storms, glaciers and everlasting snows. The Teberda Biospherical State Nature Reserve harbors 43 species of mammals. The tallest tree (60 m) measured in the expedition was Nordmann’s Fir, which is considered tallest species in Russia. The explorers visited the gorge of Gonachkhir River and the Kyzgych gorge. The Kyzgych gorge is strictly protected regime where flock of aurochs lives in the wild. Here, the team found Lonicera steveniana Fisch. ex Pojark for the first time. They were lucky enough to discover Acer tataricum L. and Euonymus nanus Bieb. in Razvalka mountain. Gennady A. Firsov, G. A. (2017) Botanical expedition in mountains of Caucasus in 2013. Conservation Science, 1: 1-9.